2002
DOI: 10.1007/s00204-002-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and unspecific protein binding of the xenoestrogens bisphenol A and daidzein

Abstract: Physiological toxicokinetic (PT) models are used to simulate tissue burdens by chemicals in animals and humans. A prerequisite for a PT model is the knowledge of the chemical's distribution among tissues. This depends on the blood flow and also on the free fraction of the substance and its tissue:blood partition coefficients. In the present study we determined partition coefficients in human tissues at 37 degrees C for the two selected xenoestrogens bisphenol A (BA) and daidzein (DA), and their unspecific bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…BPA is moderately lipophilic (Staples et al , 1998). In in vitro studies, human adipose tissue had the highest BPA concentration (Csanády et al , 2002; Geens et al , 2012). Thus, BPA storage in fat under certain conditions may be biologically plausible.…”
Section: Discussionmentioning
confidence: 99%
“…BPA is moderately lipophilic (Staples et al , 1998). In in vitro studies, human adipose tissue had the highest BPA concentration (Csanády et al , 2002; Geens et al , 2012). Thus, BPA storage in fat under certain conditions may be biologically plausible.…”
Section: Discussionmentioning
confidence: 99%
“…However, Krieter et al [33] showed that considerable amounts of BPA were eluted from dialyzers with polysulfone membranes in 180 min of simulating (in vitro) dialysis conditions with sterile water at body temperature. Previous studies had already shown that diferent polysulfone membranes leach varying amounts of BPA [31][32][33][34][35][36][37]. Obviously, this is also true for polysulfone membranes from the same manufacturer, indicating variations in diferent polysulfone lots or diferent extraction processes during iber spinning.…”
Section: Housing)mentioning
confidence: 94%
“…Moreover, a tissue/blood partition coeicient of 1.4 for nonadipose tissues and 3.3 for fat tissues further compromises the dialyzability of BPA [36], implying a concentration gradient highly in favor of driving BPA from dialysate to patient's blood.…”
Section: Housing)mentioning
confidence: 99%
“…The bound or inactive form of BPA represents 90–95% of total BPA in the blood 137139 , whereas 80% of total DEHP is bound to lipoproteins and albumin 140142 . Since many in vitro and ex vivo studies are conducted in serum-free or low albumin-containing solutions, additional studies are warranted to determine whether protein binding diminishes the bioavailability of these chemicals to such an extent that cardiotoxicity is irrelevant.…”
Section: Questions Remainingmentioning
confidence: 99%